Caribbean Report 06-01-1997 - Orr, Carol (anchor); Panday, Basdeo (interviewee); Fraser, Tony (correspondent); Ranneberger, Michael (interviewee); Birns, Larry (interviewee); King, Erskine (interviewee); Gordon, Warren (correspondent) (The British Broadcasting Corporation, 1997)
This report deals with the fact that TTUTA, the Trinidad and Tobago Unified Teachers Association is claiming a 70% success rate for its two day strike action. The significance of the Group Against the Abandonment of Children and reasons and legality of the strike are discussed. The next segment deals with the fact that a spokesman on Cuban Affairs in the US State Department is down playing a decision by US President Clinton to postpone for another six months, title three of the Helms-Burton Law. Title 3 and its implications are given at length. The following segment discusses Air Jamaican’s plans to begin its schedule service to the Eastern Caribbean. Approval was granted by the US Department of Transportation. The next segment states that the West Indies Cricket team has appeared to reverse its fortunes of the tour to Australia. Possible reasons are given for this. The final segment highlights that an educational textbook filled with sexist and racist slurs have provoked widespread outrage and there has been a call for its immediate removal by human rights groups as well as students.
1. Headlines (00:00-00:26)
2. The Trinidad and Tobago Unified Teachers Association is claiming a 70 % success rate for its two days strike action which began today (00:32-04:07)
3. A Cuban specialists says Clinton's postponement of title three of Helms-Burton amongst to an appeasement to trade allies (04:08-09:39)
4. Air Jamaica has announced it has received the final clearance to begin its schedule service to the Eastern Caribbean next month (09:41-10.05)
Keywords: Clinton, Bill, 1946-; Trinidad and Tobago Unified Teachers Association.; Strikes and lockouts -- Trinidad and Tobago.; United States -- Cuban Liberty and Democratic Solidarity (LIBERTAD) Act of 1996.; Airlines -- Caribbean Area.; Cricket -- Tournaments -- West Indies.; Cricket -- Tournaments -- Australia.; Textbooks -- Censorship.; Racism in textbooks.; Abandoned children.; Helms-Burton; Group Against the Abandonment of Children.